2008
DOI: 10.1007/s10096-008-0548-9
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant tuberculosis: rapid detection of resistance to rifampin and high or low levels of isoniazid in clinical specimens and isolates

Abstract: The aim of the present study was to evaluate a new improved multiplex polymerase chain reaction (PCR) hybridisation assay to detect multidrug-resistant tuberculosis. The assay, developed to detect rifampin (rpoB) and isoniazid (katG) gene mutations causing Mycobacterium tuberculosis resistance, was recently extended to include inhA gene mutations that code for low-level isoniazid resistance. Interpretable results were obtained in 115 isolates and in all smear-positive clinical specimens. Rifampin resistance wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
31
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 25 publications
6
31
1
1
Order By: Relevance
“…This test is useful due to its accuracy and specificity, as well as its short turnaround time and ease of use. Previous studies have demonstrated that the GenoType MTBDRplus test had outstanding performance: 91.7% to 100% accuracy in detecting RIF resistance, 34.6% to 94.6% accuracy in detecting INH resistance, and 92% to 100% accuracy in detecting MDR (1,4,6,10,15,21). In comparison, the GenoType MTBDRplus test identified 95.4% of RIF-resistant isolates, 81.8% of INH-resistant isolates, and 78.5% of MDR isolates in our study.…”
Section: Discussionmentioning
confidence: 38%
See 2 more Smart Citations
“…This test is useful due to its accuracy and specificity, as well as its short turnaround time and ease of use. Previous studies have demonstrated that the GenoType MTBDRplus test had outstanding performance: 91.7% to 100% accuracy in detecting RIF resistance, 34.6% to 94.6% accuracy in detecting INH resistance, and 92% to 100% accuracy in detecting MDR (1,4,6,10,15,21). In comparison, the GenoType MTBDRplus test identified 95.4% of RIF-resistant isolates, 81.8% of INH-resistant isolates, and 78.5% of MDR isolates in our study.…”
Section: Discussionmentioning
confidence: 38%
“…The World Health Organization and partners have endorsed the use of the molecular test GenoType MTBDRplus (Hain Lifescience GmbH, Nehren, Germany) for rapid detection of high-risk MDR-TB cases, even directly from certain clinical specimens (1,4,6,10,15,21). The GenoType MTBDRplus test is a PCR-based amplification and reverse blotting assay that employs specific probes hybridized to nitrocellulose strips to detect RIF and INH resistance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The line probe assays (LPA) GenoType MTBDRplus (Hain Lifescience, Nehren, Germany) and INNO-LiPA Rif.TB (InnoGenetics, Ghent, Belgium) were carried out as previously described (7)(8)(9). With these kits, PCR of rpoB is followed by hybridization of mutants to a membrane strip.…”
Section: P Atients With Tuberculosis (Tb) That Harbor Drug-susceptiblementioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40][41][42] Conceptually similar to the INNO-Lipa Rif.tb assay, the MTBDRplus assay has been reported to have a diagnostic sensitivity of approximately 94% for detecting M tuberculosis DNA in smear-positive respiratory specimens. 33 It is of interest that most clinical evaluations of this device have focused on its use for susceptibility testing, not detection of M tuberculosis, so the performance characteristics for the latter use are less well defined.…”
Section: Line Probe Assaysmentioning
confidence: 99%